Enhanced nonlinear optical characteristics of copper-ion-doped double crossover DNAs. Issue 43 (15th October 2015) - Park, Byeongho; Lee, Byung Jic; Dugasani, Sreekantha Reddy; Cho, Youngho; Kim, Chulki; Seo, Minah; Lee, Taikjin; Jhon, Young Min; Choi, Jaebin; Lee, Seok; Park, Sung Ha; Jun, Seong Chan; et al.
Abstract : The nonlinearity of double crossover DNAs investigated by Z -scan and four-wave mixing experiments was considerably enhanced with copper-ion doping. Abstract : The modification of deoxyribonucleic acid (DNA) samples by sequencing the order of bases and doping copper ions opens the possibility for the design of novel nanomaterials exhibiting large optical nonlinearity. We investigated the nonlinear characteristics of copper-ion doped double crossover DNA samples for the first time to the best of our knowledge by using Z -scan and four-wave mixing methods. To accelerate the nonlinear characteristics, we prepared two types of unique DNA nanostructures composed of 148 base pairs doped with copper ions with a facile annealing method. The outstanding third-order nonlinear optical susceptibility of the copper-ion-doped DNA solution, 1.19 × 10 −12 esu, was estimated by the conventional Z -scan measurement, whereas the four-wave mixing experiment was also investigated. In the visible spectral range, the copper-ion-doped DNA solution samples provided competent four-wave mixing signals with a remarkable conversion efficiency of −4.15 dB for the converted signal at 627 nm. The interactions between DNA and copper ions contribute to the enhancement of nonlinearity due to structural and functional changes. The present study signifies that the copper-ion-doped double crossover DNA is a potential candidate as a highly efficient novel material for further nonlinear optical applications.